Proposing a Study to Promote the Intention of Online Purchasing of Organic Agricultural Products in the Northside of Vietnam - Trinh Hoai , Son; Vu Thi , Dieu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study surveyed 730 residents in the Northside of Vietnam to propose recommendations for promoting the intention to purchase organic agricultural products online among consumers. Based on the TAM and TPB models, using statistical analysis methods such as EFA and linear regression analysis with SPSS 26.0, six factors affecting the intention to purchase organic agricultural products online of consumers were identified, including expectations of price, food safety, product quality, social influence, trust, and quality of after-sales service. These results provide a basis for proposing recommendations to enhance production capacity, sales, make appropriate decisions, actions for businesses, consumers, and relevant management agencies regarding organic agricultural products.